Purpose, goals, and principles of digital university design (Journal of Finance, Business and Management Studies, 2026)
The digitalization of education is a fundamental transformation of traditional learning models, providing flexibility, accessibility, and personalization of the educational process. The concept of a digital university involves the integration of information and communication technologies (ICT) into all aspects of its activities, including the organization of the learning process, knowledge management, and interaction between students, teachers, and administration. The article examines the purpose, goals, and principles of digital university design, analyzes the key socio-pedagogical conditions for its implementation, and considers the impact of modern technologies on the efficiency of the educational process. The main advantages of a digital university are identified, including automation of learning processes, adaptive learning, use of a virtual environment, and integration of electronic educational resources. The main challenges faced by digital universities are also analyzed, including the need to adapt educational programs, develop effective methods of interaction between participants in the educational process, and ensure quality educational content. The article emphasizes that a digital university is a promising model of education that allows creating an innovative, adaptive, and effective learning system that meets the requirements of the modern digital society.
Keywords: digital university; digitalization; adaptive learning; educational digitalization; electronic educational resources